Development of an Android-Based Application for Technical Drawing to Enhance Learning Outcomes - Krisdiantoro, Dwiki; Wijaya, Burhan Rubai; Suryatna, Bambang Sugeng (Universitas Negeri Semarang, 2024)
This study is motivated by challenges in the teaching and learning process of technical drawing, including low student engagement, ineffective lesson hours, suboptimal learning media, and previous student achievement scores below 80%. The research aims to develop an Android-based learning media application, JAGAR, for teaching single-story house plan drawing, assess its feasibility, evaluate its practicality, and compare its effectiveness with other instructional methods in improving learning outcomes. The study employs the ADDIE development model and is conducted at SMK Negeri 7 Semarang, specifically in the Grade XI Building Construction, Sanitation, and Maintenance Program. The sample consists of 70 students divided into two classes, each subjected to different instructional approaches. The findings indicate that the JAGAR learning application is both feasible and practical based on evaluations by subject matter experts and teachers. Additionally, its implementation proves to be more effective than conventional methods. The study concludes that utilizing the JAGAR application significantly enhances student learning outcomes and motivation. The novelty of this research lies in the integration of instructional videos, quizzes, and job sheets within the learning media.